2016
DOI: 10.1002/mds.26828
|View full text |Cite
|
Sign up to set email alerts
|

A novelRAB39Bgene mutation in X-linked juvenile parkinsonism with basal ganglia calcification

Abstract: X-linked juvenile parkinsonism could be caused by a RAB39B mutation, and basal ganglia calcification may be a novel clinical feature of RAB39B-related parkinsonism. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 28 publications
1
50
0
Order By: Relevance
“…Recently, our team also identified a novel mutation of Rab39b (c.536 dup A) in a family, of which the patients displayed juvenile parkinsonism and mental retardation syndromes. Moreover, the brain magnetic resonance imaging (MRI) and computed tomography (CT) scans of both patients showed calcification in the basal ganglia, which was never reported in the previous cases (Shi et al, 2016). According to the latest study, the complex formed by C9ORF72, WDR41 and SMCR8 worked as a GEF for Rab39b as well as Rab8a, which suggested that Rab39b might be involved in the autophagy regulation (Sellier et al, 2016).…”
Section: The Interactions Between Rabs and Different Pd-related Genessupporting
confidence: 49%
See 2 more Smart Citations
“…Recently, our team also identified a novel mutation of Rab39b (c.536 dup A) in a family, of which the patients displayed juvenile parkinsonism and mental retardation syndromes. Moreover, the brain magnetic resonance imaging (MRI) and computed tomography (CT) scans of both patients showed calcification in the basal ganglia, which was never reported in the previous cases (Shi et al, 2016). According to the latest study, the complex formed by C9ORF72, WDR41 and SMCR8 worked as a GEF for Rab39b as well as Rab8a, which suggested that Rab39b might be involved in the autophagy regulation (Sellier et al, 2016).…”
Section: The Interactions Between Rabs and Different Pd-related Genessupporting
confidence: 49%
“…Parkinson’s disease (PD) is the second most prevalent chronic neurodegenerative disorder of aging, clinically characterized by motor symptoms including resting tremor, muscle rigidity, bradykinesia, postural instability and various non-motor symptoms (Shi et al, 2016). The most evident pathological features are the progressive degeneration of dopaminergic neurons and axonal projections in the substantia nigra and the wide spreading of eosinophilic Lewy bodies whose cardinal component is α-synuclein detected in some surviving neurons (Goedert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant associations at different loci—Discs large homolog of 2 ( DLG2 ), Sipa1-like protein ( SIPA1L2 ), Serine/Theonine kinase 39 ( STK39 ), Vacuolar protein sorting 13 homolog C ( VPS13C ), Ric-like protein without CAAX motif 2 ( RIT2 ), BST1 , PARK16 —have been found in Asians vs. Europeans, together with allelic heterogeneity at LRRK2 and at six other loci including MAPT and GBA-SYT11 [50]. Some other candidate genes have been recently reported to be associated with PD in different cohorts (i.e., RAD51B [39], DYRK1A [53], CHCHD2 [54], VPS35 [55], RAB39B [56], TMEM230 [57]).…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
“…RAB39B c.536dupA (p.E179fsX48) was identified in a small Chinese family with two male patients who had learning difficulty from childhood and mild intellectual disability [72]. Both developed tremor and rigidity at age 10 and 12 years, progressing to moderate or severe PD by ages 20 and 58 years.…”
Section: New Genes For Recessive and X-linked Pd Or Parkinsonismmentioning
confidence: 99%